Illocutionary Acts Performed by Meilin in “Turning Red” the Movie - Widyasari, Ketut Monica; Sukarini, Ni Wayan; Maharani, Sang Ayu Isnu (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This analysis entitled